ChemInform Abstract: Cu1.5Mn1.5O4 Spinel: A Novel Anode Material for Lithium‐Ion Batteries. Issue 35 (August 2016) - Quan, Jingbin; Mei, Lin; Ma, Zheng; Huang, Jichun; Li, Decheng
Abstract: Cu1.5 Mn1.5 O4 is prepared by spray drying of an aqueous solution of Cu(OAc)2, Mn(OAc)2, and citric acid with an outlet temperature of 185 °C followed by pre‐sintering in air (300 °C, 3 h).